2010
DOI: 10.3109/08958371003686016
|View full text |Cite
|
Sign up to set email alerts
|

Long-term pulmonary complications of chemical warfare agent exposure in Iraqi Kurdish civilians

Abstract: The Iraqi government used a range of chemical weapons, including blistering and nerve agents, against Iraqi Kurdish civilians in the 1980s. Few data exist about the long-term respiratory consequences of this exposure. In this study, Kurdish subjects with a history of exposure to chemical weapons were invited to attend a clinical assessment, including a review of their history, physical examination, and a high-resolution computed tomography (CT) of the thorax. Blistering at the time of exposure was used to defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 15 publications
(19 reference statements)
1
25
0
2
Order By: Relevance
“…Most common problems in all injured Iranian survivors exposed to SMin the Iran-Iraq war have been reported in previous studies [1,4]. Similar to those symptoms we observed, Ghanei et al reported a high incidence of respiratory symptoms in chemical weapon-exposed populations in Iraqi Kurdistan [9]. The use of blistering agents by the Iraqi army still is not known, but a history of blistering at the time of exposure was related, followed by delayed destructive lesions in the ocular surface and cornea, which led to progressive visual deterioration and ocular irritation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Most common problems in all injured Iranian survivors exposed to SMin the Iran-Iraq war have been reported in previous studies [1,4]. Similar to those symptoms we observed, Ghanei et al reported a high incidence of respiratory symptoms in chemical weapon-exposed populations in Iraqi Kurdistan [9]. The use of blistering agents by the Iraqi army still is not known, but a history of blistering at the time of exposure was related, followed by delayed destructive lesions in the ocular surface and cornea, which led to progressive visual deterioration and ocular irritation.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the most interesting finding was that when an ocular damaging process happened, it developed more quickly in the Iraqi Kurdish population than in Iranian subjects. A possible explanation for this might be that Iranian physicians were familiar with SM effects, in addition to the early application of countermeasures such as removing contaminated clothing, washing exposed tissues, and applying neutralizing agents could have been expected to reduce complications and encourage a rapid recovery in Iranian subjects [9,15]. However, there were other factors that could modulate exposure severity, such as the increased dose of chemical agents, different environmental conditions and distance from the attack location in the Iraqi Kurdish population.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary exposure to these vesicants results in extensive tissue damage and persistent bronchiolitis, which progresses to fibrosis (3,4). Mortality and long-term morbidity following exposure to mustards are a consequence of alkylation and crosslinking of critical nucleophilic sites in target tissues including DNA and proteins.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Life style, psychiatric parameters, and socioeconomic status are some factors affected by these clinical complications. Many previously performed studies have evaluated the lung complications of these patients (33,36,37), and showed that the frequency of lung complications in mus-tard gas-intoxicated patients was about 100%.…”
Section: Discussionmentioning
confidence: 99%